2009 IEEE Nuclear Science Symposium Conference Record (NSS/MIC) 2009
DOI: 10.1109/nssmic.2009.5401682
|View full text |Cite
|
Sign up to set email alerts
|

rSPECT: A compact gamma camera based SPECT system for small-animal imaging

Abstract: We have developed a compact and modular gamma camera system and assessed its performance when used on a small-animal SPECT prototype (rSPECT). Each camera consists of a Hamamatsu H-8500 position sensitive photomultiplier tube coupled to a 30 x 30 NaI (Tl) scintillator array (1.4mm x 1.4mm x 6mm crystal size) and electronics for pre-processing and matching the detector signals to an in-house developed data acquisition system. The camera components are enclosed in a lead-shielded case with a receptacle to insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…We used the same parallel-hole collimator that is used for small animal SPECT system [37]. This was a low-energy high-resolution parallel-hole collimator (LEHR) made of lead.…”
Section: Configuration Of Small Animal Spect Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the same parallel-hole collimator that is used for small animal SPECT system [37]. This was a low-energy high-resolution parallel-hole collimator (LEHR) made of lead.…”
Section: Configuration Of Small Animal Spect Systemsmentioning
confidence: 99%
“…The spatial resolution and sensitivity values for a centered source in air, positioned 10, 20, 30, 40, and 50 mm from the collimator, were obtained. The FWHM of the point spread function (PSF) was determined by fitting a Gaussian function of the count profiles and by direct calculation from the profile data using a linear interpolation between the points above and below the half-maximum value [2,37]. To more accurately determine the resolution at each position, we repeated the measurements five times at each position.…”
Section: Comparison Of System Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a signal of DT cycles duration is generated at the BUSY output of this component in order to disable the associated stabilizer components during the processing of the current event. For the implementation of a SPECT system called rSPECT (Lage et al 2009b), we used the same components shown in figure 5 Each ADC module contain 16 channels (12 bit per channel) whose internal topology groups the channels in sets of 4 with an independent gate input for each of them. These ADC boards are prepared to work almost independently since they only need the gate signal to start the data acquisition, conversion and transmission.…”
Section: Data Acquisition System Prototypementioning
confidence: 99%
“…Al igual que en el capítulo anterior, se han añadido un anexo (Anexos 5.1) que contiene una comparativa del sistema SPECT desarrollado con otros sistemas comerciales. Este capítulo está basado en Lage et al, 2009d;Lage et al, 2009e;Lage et al, 2009f).…”
Section: Aunque En Los úLtimos Años Grandes Casas Comerciales Como Ge...unclassified